2013
DOI: 10.1021/jp4023986
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Quantum States Created by One Photon Absorption: Pulsed Coherent vs Pulsed Incoherent Light

Abstract: We analyze electronically excited nuclear wave functions and their coherence when subjecting a molecule to the action of natural, pulsed incoherent solar-like light, and to that of ultrashort coherent light assumed to have the same center frequencies and spectral bandwidths. Specifically, we compute the spatio-temporal dependence of the excited wave packets and their electronic coherence for these two types of light sources, on different electronic potential energy surfaces. The resultant excited state wave fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Therefore, an understanding of excitation under incoherent conditions is crucial. In such cases, the long time result of incoherent irradiation, using both quantum and classical light, leads to a mixed state of the system [3,4], a result discussed further in the literature in the context of photosynthetic light harvesting complexes [5][6][7]. However, work has been done, for example, on incoherent or noisy perturbations in quantum optics where some have found that incoherent or noisy electric fields can generate transient coherences in three level atoms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an understanding of excitation under incoherent conditions is crucial. In such cases, the long time result of incoherent irradiation, using both quantum and classical light, leads to a mixed state of the system [3,4], a result discussed further in the literature in the context of photosynthetic light harvesting complexes [5][6][7]. However, work has been done, for example, on incoherent or noisy perturbations in quantum optics where some have found that incoherent or noisy electric fields can generate transient coherences in three level atoms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This is distinctly different from the results of pulsed laser excitation, as most recently shown for coherent vs. incoherent excitation with the same spectrum [6]. Thus, the coherent pulsed laser experiments provide important insight into the nature of the system Hamiltonian and of the coupling of the system to the environment, but describe coherences in dynamics that is dramatically different than natural processes [4,5,[7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 75%
“…As shown in Refs. [1,2], the initial conditions for excitation with an incoherent light source such as the sun are the productions of a set of individual phase-unrelated eigenstates. Hence, the incoherent dynamics discussed here always exists and is being induced by all light sources.…”
Section: ½E ð2þmentioning
confidence: 99%
“…In addition to this type of incoherent dynamics, there are coherent dynamics which follow excitations with coherent pulses, arising from the de-phasing of each ME with respect to all others. Such coherent pulsed excitations tell us, however, nothing about the situation with incoherent sources, where no coherent dynamics is exhibited [1,2].…”
Section: ½E ð2þmentioning
confidence: 99%
See 1 more Smart Citation